KURIKULUM BERBASIS GENDER (Membangun Pendidikan yang Berkesetaraan) - Adriana, Iswah (JURNAL TADRIS STAIN PAMEKASAN, 2009)
Abstrak: Essentially education includes the principles of gender equity. Biased gender in education results on unobtionable of educational goals. For that reason, it is required an equal education where the curriculum of the institution integrates gender within its subjects and lectures. Through this paper, the writer will explain the importance of gender equity in education in relation to curriculum and its application.